Long‐term outcomes, secondary malignancies and stem cell collection following bendamustine in patients with previously treated non‐Hodgkin lymphoma. (17th April 2017) - Martin, Peter; Chen, Zhengming; Cheson, Bruce D.; Robinson, Katherine S.; Williams, Michael; Rajguru, Saurabh A.; Friedberg, Jonathan W.; van der Jagt, Richard H.; LaCasce, Ann S.; Joyce, Robin; Ganjoo, Kristen N.; Bartlett, Nancy L.; et al.
Summary: Despite the long history of bendamustine as treatment for indolent non‐Hodgkin lymphoma, long‐term efficacy and toxicity data are minimal. We reviewed long‐term data from three clinical trials to characterize the toxicity and efficacy of patients receiving bendamustine. Data were available for 149 subjects at 21 sites. The median age was 60 years at the start of bendamustine (range 39–84), and patients had received a median of 3 prior therapies. The histologies included grades 1–2 follicular lymphoma (FL; n  = 73), grade 3 FL ( n  = 23), small lymphocytic lymphoma ( n  = 20), marginal zone lymphoma ( n  = 15), mantle cell lymphoma ( n  = 9), transformed lymphomas ( n  = 5), lymphoplasmacytic lymphoma ( n  = 2) and not reported ( n  = 2). The median event‐free survival was 14·1 months. Nine of 12 attempted stem cell collections were successful. With a median follow‐up of 8·9 years, 23 patients developed 25 cancers, including 8 patients with myelodysplastic syndrome/acute myeloid leukaemia. These data provide important information regarding the long‐term toxicity of bendamustine in previously treated patients. A small but meaningful number of patients achieved durable remissions following bendamustine. These rigorously collected, patient‐level, long‐term follow‐up data provide reassurance that bendamustine or bendamustine plus rituximab is associated with efficacy and safety for patients with relapsed or refractory indolent non‐Hodgkin lymphoma.